Murine but Not Human Basophil Undergoes Cell-Specific Proteolysis of a Major Endoplasmic Reticulum Chaperone - Liu, Bei; Staron, Matthew; Li, Zihai (PLOS ONE, 2012)
Introduction Basophil has been implicated in anti-parasite defense, allergy and in polarizing TH2 response. Mouse model has been commonly used to study basophil function although the difference between human and mouse basophils is underappreciated. As an essential chaperone for multiple Toll-like receptors and integrins in the endoplasmic reticulum, gp96 also participates in general protein homeostasis and in the ER unfolded protein response to ensure cell survival during stress. The roles of gp96 in basophil development are unknown. Methods We genetically delete gp96 in mice and examined the expression of gp96 in basophils by Western blot and flow cytometry. We compared the expression pattern of gp96 between human and mouse basophils. Results We found that gp96 was dispensable for murine basophil development. Moreover, gp96 was cleaved by serine protease(s) in murine but not human basophils leading to accumulation of a nun-functional N-terminal ∼50 kDa fragment and striking induction of the unfolded protein response. The alteration of gp96 was unique to basophils and was not observed in any other cell types including mast cells. We also demonstrated that the ectopic expression of a mouse-specific tryptase mMCP11 does not lead to gp96 cleavage in human basophils. Conclusions Our study revealed a remarkable biochemical event of gp96 silencing in murine but not human basophils, highlighting the need for caution in using mouse models to infer the function of basophils in human immune response. Our study also reveals a novel mechanism of shutting down gp96 post-translationally in regulating its function.